Recording and analysing physical control variables used in clarinet playing: A musical instrument performance capture and analysis toolbox (MIPCAT) - Almeida, André; Li, Weicong; Schubert, Emery; Smith, John; Wolfe, Joe (Frontiers in Signal Processing, 2023)
Measuring fine-grained physical interaction between the human player and the musical instrument can significantly improve our understanding of music performance. This article presents a Musical Instrument Performance Capture and Analysis Toolbox (MIPCAT) that can be used to capture and process the physical control variables used by a musician while performing music. This includes both a measurement apparatus with sensors and a software toolbox for analysis. Several of the components used here can also be applied in other musical contexts. The system is here applied to the clarinet, where the instrument sensors record blowing pressure, reed position, tongue contact and sound pressures in the mouth, mouthpiece, and barrel. Radiated sound and multiple videos are also recorded to allow details of the embouchure and the instrument’s motion to be determined. The software toolbox can synchronise measurements from different devices, including video sources, extract time-variable descriptors, segment by notes and excerpts, and summarise descriptors per note, phrase, or excerpt. An example of its application shows how to compare performances from different musicians.